DESIGNING AN AI CHATBOT (STYLESAVVY) FOR CHOOSING CLOTHES FASHION BASED ON SKIN TONE AT XI-XIU STORE - Ayuningsih, Ekatri Ayuningsih; Lubis, Sevana Rizki; Tembusai, Zulkarnain (Universitas Budi Darma, 2024)
Chatbot is a computer program with artificial intelligence to interact with humans through conversation, provide responses, and offer services. Its function is to provide services or information to users in a way that resembles human conversation. This study can give recommandation towaards fashion and makeover based on skin tone and enhance confidence about self performance. This study did not only provide recommendation by picture and description, but also a link to view the video that can be seen by the users. The result of this study gives varies benefits for researcher in understanding further about AI technology users in fashion industry, then for the company and education institution in progressing service and relevant curriculum. On the other side, this study contributes on AI technology development in the future, especially in terms of fashion and aesthetic.